Comparison of Standard, Tubular, and Banana Swing Arm Designs for Converting Scooter-Type Motorcycles into Electric Vehicles - Rahmadi, Apri; Mursalin, Mursalin; Ahmad Bustami, Riyan (Diponegoro University, 2024)
The percentage of motorcycle population in Indonesia reaches 82% of the total number of motorized vehicles. Almost all of these motorcycles are gasoline-powered vehicles, which ultimately consume a significant amount of fossil fuels and contribute to approximately 5% of greenhouse gas emissions. In addressing this issue, the government is promoting a motor vehicle electrification program. Motorcycles are predominantly automatic scooter types, presenting a significant opportunity for the vehicle electrification program. This research aims to design a swing arm used in converting automatic scooter-type motorcycles into electrically powered ones. In this study, three different swing arm designs were created: standard type, tubular type, and banana type. Stress analysis was conducted on these three swing arms under a load of 180 kg. The results indicate that the banana-type swing arm is the best design due to its superior strength and lighter weight. The designed banana swing arm has a weight of only 4.37 kg, experiences von Mises stress of 73.58 MPa, displacement of 0.46 mm, and a safety factor of 2.81